Variability in Length of Crop Growing Period Causing Agricultural Vulnerability in India - Ramachandran, Kaushalya; S, Shubhasmita; Haritha, A (Annals of Arid Zone, 2019)
Satellite-data based Normalized Difference Vegetation Index (NDVI) can indicate state of agriculture, crop vigour and hence can also be used to assess agricultural vulnerability. Analysis of trends in NDVI for a given region can indicate the factors that cause variability and the drivers that impart vulnerability to agriculture. One such driver is variability in Length-of-Crop-Growing – Period (LGP). A methodology was developed to determine LGP from time-series NDVI datasets from Start-of-Season or greening-up phase to End-of-Season or drying-up phase. Public domain data like NOAA-AVHRR based GIMMS data product (1982-2006) and MODIS-TERRA data (2000- 2013) were used to analyse variations in LGP contributing to agricultural vulnerability in various agro-ecological sub-regions (AESR) in Peninsular India. Study carried out at ICAR-CRIDA under NICRA indicates the variable trends in LGP and its impact on agricultural production leading to agricultural vulnerability in India. Key words: LGP, NDVI, agricultural vulnerability, crop phenology, AESR, rainfed agriculture.